The effects of exercise training on HPA-axis reactivity and autonomic response to acute stress – a randomized controlled study - Arvidson, Elin; Jonsdottir, Ingibjörg H (Region Västra Götaland, 2019)
The aim of the present trial was to study the effects of a six-month aerobic exercise intervention on the physiological response to acute laboratory stress. A two-armed RCT including untrained but healthy individuals aged 20-50 years was conducted. Assessments included a peak oxygen uptake test and a psychosocial stress test (the Trier Social Stress Test). A total of 88 participants went through both baseline and follow-up measures (48 in the intervention group and 40 in the control group) with an even distribution of women and men (20/28 in the intervention group and 18/22 in the control group, respectively). Outcome measures were adrenocorticotrophic hormone, cortisol, systolic- and diastolic blood pressure and heart rate responses to acute psychosocial stress.

Outcome measures: adrenocorticotrophic hormone, cortisol, systolic- and diastolic blood pressure and heart rate responses to acute psychosocial stress.

Datamaterialet har använts i en studie som syftar till att undersöka effekterna av en träningsintervention på fysiologisk respons på akut stress. Totalt 88 individer ingår i materialet, samtliga har genomgått både baslinje- och uppföljande mätningar. Variablerna i materialet är bland annat ACTH, kortisol, syreupptag, puls och blodtryck.
The effects of exercise training on HPA-axis reactivity and autonomic response to acute stress – a randomized controlled study - Effekter av fysisk träning på HPA-axelreaktivitet och autonom respons på akut stress - en randomiserad kontrollerad studie
Keywords: Physical Education and Training; Fysisk fostran och träning; Randomized Controlled Trial; Randomiserad klinisk prövning [Publikationstyp]; physiological stress; psykosocial stress; HPA-axis; HPA-axeln; acute stress; akut stress; Medical and Health Sciences; Medicin och hälsovetenskap